Nanoscale patterning of a self-assembled monolayer by modification of the molecule–substrate bond - Shen, Cai; Buck, Manfred (Beilstein Journal of Nanotechnology, 2014)
The intercalation of Cu at the interface of a self-assembled monolayer (SAM) and a Au(111)/mica substrate by underpotential deposition (UPD) is studied as a means of high resolution patterning. A SAM of 2-(4'-methylbiphenyl-4-yl)ethanethiol (BP2) prepared in a structural phase that renders the Au substrate completely passive against Cu-UPD, is patterned by modification with the tip of a scanning tunneling microscope. The tip-induced defects act as nucleation sites for Cu-UPD. The lateral diffusion of the metal at the SAM–substrate interface and, thus, the pattern dimensions are controlled by the deposition time. Patterning down to the sub-20 nm range is demonstrated. The difference in strength between the S–Au and S–Cu bond is harnessed to develop the latent Cu-UPD image into a patterned binary SAM. Demonstrated by the exchange of BP2 by adamantanethiol (AdSH) this is accomplished by a sequence of reductive desorption of BP2 in Cu free areas followed by adsorption of AdSH. The appearance of Au adatom islands upon the thiol exchange suggests that the interfacial structures of BP2 and AdSH SAMs are different.
Keywords: copper; electrodeposition; gold adatoms; nanolithography; negative resist